Cyclin-dependent kinase inhibitors as anticancer drugs - Kryštof, Vladimír; Uldrijan, Stjepan (Current drug targets, 2010)
Poor therapeutic outcomes and serious side effects, together with acquired resistance to multiple drugs, are common problems of current cancer therapies. Therefore, there is an urgent need for new cancer-targeted drugs, which has led (inter alia) to the development of molecules that can specifically inhibit cyclin-dependent kinases (CDKs). In addition to their cell cycle regulatory functions, CDKs, especially CDK7 and CDK9, play important roles in the regulation of RNA polymerase II-mediated transcription. Here, we report on progress in the preclinical development of CDK inhibitors and their anticancer activities. Special attention is paid to the action mechanisms of the pan-specific CDK inhibitors flavopiridol and roscovitine, which have already entered phase II clinical trials as treatments for various tumours. The links between their ability to inhibit transcription and sensitisation of some types of cancer to apoptosis, mechanisms leading to p53 activation, and their synergistic cooperation with common DNA damaging drugs are also discussed. It has been demonstrated that drug-resistant cancer cells can arise during therapeutic application of small molecule protein kinase inhibitors. Clinical resistance to CDK inhibitors has not yet been described, but by comparing CDKs to other kinases, and CDK inhibitors to other clinically used protein kinase inhibitors, we also discuss possible mechanisms that could lead to resistance to CDK inhibitors.
Keywords: lékové transportní systémy; preklinické hodnocení léčiv; Humans; protinádorové látky; Clinical Trials as Topic; Neoplasms; Enzyme Inhibitors; lidé; Drug Evaluation, Preclinical; Drug Delivery Systems; inhibitory enzymů; Cyclin-Dependent Kinases; racionální návrh léčiv; Antineoplastic Agents; cyklin-dependentní kinasy; chemorezistence; Apoptosis; apoptóza; klinické zkoušky jako téma; Drug Design; Drug Resistance, Neoplasm; nádory